2020
DOI: 10.3389/fped.2020.00235
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Effusion/Cardiac Tamponade Induced by Peripherally Inserted Central Catheters in Very Low Birth Weight Infants: A Case Report and Literature Review

Abstract: Background: Although pericardial effusion/cardiac tamponade (PCE/CT) is a rare complication of peripherally inserted central catheters (PICCs), with an incidence of 0. 07-2%, it is associated with high mortality and is often life threatening. We sought to improve understanding of PICC-induced PCE/CT among pediatricians. Case presentation:The clinical data of PICC-associated PCE/CT in a very low birth weight (VLBW) infant were summarized, and the relevant literature was also reviewed. Conclusions:In VLBW infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Nadroo et al found that soft tissue around the catheter would be squeezed during adduction of the shoulder joint or flexion of the elbow, and the venous catheter would displace from the heart; whereas concurrent shoulder joint adduction and elbow flexion would result in its retraction towards the heart. [3] Therefore, maintaining arm adduction and elbow flexion during X-ray positioning can effectively reduce the risk of pericardial effusion caused by PICC displacement into the right atrium due to arm movement, [10] and the exposed end of the PICC should be securely affixed with adhesive tape to minimize catheter migration. [4,9] To ensure accurate positioning of the catheter tip, X-ray or cardiovascular ultrasonography should be performed at least twice a week.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nadroo et al found that soft tissue around the catheter would be squeezed during adduction of the shoulder joint or flexion of the elbow, and the venous catheter would displace from the heart; whereas concurrent shoulder joint adduction and elbow flexion would result in its retraction towards the heart. [3] Therefore, maintaining arm adduction and elbow flexion during X-ray positioning can effectively reduce the risk of pericardial effusion caused by PICC displacement into the right atrium due to arm movement, [10] and the exposed end of the PICC should be securely affixed with adhesive tape to minimize catheter migration. [4,9] To ensure accurate positioning of the catheter tip, X-ray or cardiovascular ultrasonography should be performed at least twice a week.…”
Section: Discussionmentioning
confidence: 99%
“…[9] There were also reports of successful rescue by either repositioning the catheter tip away from the right atrium or direct drainage of the effusion via PICC. [10] However, once echocardiography reveals cardiac chamber compression and deformation, restricted diastole and systole, and reduced cardiac output, prompt pericardiocentesis is necessary. The subxiphoid percutaneous approach is a safer and more reliable option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A peripherally inserted central catheter (PICC) with its tip preferably in the vena cava allows for middle to long-term intravenous therapy, blood sampling, and reductions in repeated intravenous catheterizations [1,2]. Though PICC insertion is a relatively convenient and effective technique, it can cause life-threatening complications such as catheterrelated bloodstream infection [3,4] and pericardial tamponade [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%